Hubungan Kampanye New Normal dengan Tingkat Kesadaran Mahasiswa - Khansa Arifah Rahmah; Zulfebriges (Bandung Conference Series: Communication Management, 2022)
Abstract. A new outbreak that attacked humans was found in Wuhan, China, China in December 2019. This outbreak had an impact on inflammation in the respiratory tract and was known as Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-COV2) or people called it COVID. -19 (Coronavirus Disease-2019). The formulation of the problem in this study is "How big is the relationship between the new normal campaign on the @gov.sg instagram account and the level of student awareness of the 2018 Unisba fikom students?". This study aims to find out and understand how big is the relationship between awareness new normal and student awareness levels, how big is the relationship between action new normal and student awareness levels, and how big is the relationship between attitude new normal and student awareness levels on the @gov.sg Instagram account. The research method used is a quantitative method with a correlational approach. The population of this study were active students of Fikom Unisba 2018 with a total sample of 80 respondents and used a random sampling technique. Data collection techniques were carried out by distributing questionnaires. Then analyzed using inferential statistical data analysis techniques with the help of the SPSS version 25 application. From the research that has been done it can be concluded that the relationship between campaigns and awareness levels has a strong relationship, awareness and awareness levels have a strong relationship, action and awareness levels have a strong relationship. , attitude with level of awareness has a strong relationship. Overall, the new normal campaign uploaded to the @gov.sg Instagram account has a strong relationship with the level of awareness among Fikom Unisba 2018 students. Keywords: campaign, level of public awareness, stimulus response theory, new media Abstrak. Ditemukan wabah baru yang menyerang manusia di Wuhan, Tiongkok, China pada bulan Desember tahun 2019. Wabah ini membawa dampak terjadinya peradangan pada saluran pernapasan dan dikenal dengan nama Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-COV2) atau orang-orang menyebutnya dengan nama COVID-19 (Coronavirus Disease-2019). Rumusan masalah pada penelitian ini ialah “Seberapa besar hubungan kampanye new normal pada akun instagram @gov.sg dengan tingkat kesadaran mahasiswa pada mahasiswa fikom Unisba 2018?”. Penelitian ini bertujuan untuk mengetahui dan memahami seberapa besar hubungan awareness new normal dengan tingkat kesadaran mahasiswa, seberapa besar hubungan action new normal dengan tingkat kesadaran mahasiswa, dan seberapa besar hubungan attitude new normal dengan tingkat kesadaran mahasiswa pada akun Instagram @gov.sg. Metode penelitian yang digunakan adalah metode kuantitatif dengan pendekatan korelasional. Populasi dari penelitian ini merupakan mahasiswa aktif Fikom Unisba 2018 dengan jumlah sampel sebanyak 80 responden serta menggunakan teknik random sampling. Teknik pengumpulan data dilakukan dengan menyebarkan kuesioner. Lalu dianalisis menggunakan teknik analisis data statistik inferensial dengan bantuan aplikasi SPSS versi 25. Dari penelitian yang telah dilakukan dapat disimpulkan bahwa hubungan kampanye dengan tingkat kesadaran memiliki hubungan yang kuat, awareness dengan tingkat kesadaran memiliki hubungan yang kuat, action dengan tingkat kesadaran memiliki hubungan yang kuat, attitude dengan tingkat kesadaran memiliki hubungan yang kuat. Secara keseluruhan kampanye new normal yang diunggah pada akun Instagram @gov.sg memiliki hubungan yang kuat dengan tingkat kesadaran pada mahasiswa Fikom Unisba 2018. Kata Kunci: kampanye, tingkat kesadaran masyarakat, teori stimulus respon, new media.